Effects of Financial Inclusion on Access to Emergency Funds for Healthcare in the Kingdom of Saudi Arabia - Al-Hanawi MK; Chirwa GC; Kamninga TM; Manja LP (Journal of Multidisciplinary Healthcare, 2020)
Mohammed Khaled Al-Hanawi,1 Gowokani Chijere Chirwa,2 Tony Mwenda Kamninga,3 Laston Petro Manja2 1Department of Health Services and Hospital Administration, Faculty of Economics and Administration, King Abdulaziz University, Jeddah 80200, Saudi Arabia; 2Economics Department, Chancellor College, University of Malawi, Zomba, Malawi; 3Research and Policy Department, African Institute for Development Policy, Lilongwe, MalawiCorrespondence: Mohammed Khaled Al-HanawiDepartment of Health Services and Hospital Administration, Faculty of Economics and Administration, King Abdulaziz University, Jeddah 80200, Saudi ArabiaEmail mkalhanawi@kau.edu.saBackground: Having access to convenient and quality healthcare at all times is not only a human right but also a goal that many countries strive to achieve for their population. However, access to healthcare might face blocks in the presence of financial exclusions. Saudi Arabia has, over the years, continued to pursue policy and system reforms to enhance its population’s access to financial inclusion, as well as proper health coverage to improve health outcomes. This study seeks to estimate the effects of financial inclusion on the financial hardships in accessing healthcare in Saudi Arabia.Methods: This study uses a nationally representative survey conducted with 1009 adults, using the 2017 World Bank Global Findex Study data. The study estimates the conditional probability of coming up with emergency funds and the conditional probability of borrowing for medical purposes to understand access to healthcare. A composite value is created for financial inclusion using several variables for individuals’ interactions with financial institutions, such as access to financial services and loans.Results: The results revealed that financially included individuals have a higher conditional probability of both borrowing for medical purposes and coming up with emergency funds, compared to those who are financially excluded. Additionally, the study showed that individuals in low-income brackets are more likely to be financially excluded and have a reduced chance of coming up with emergency funds and borrowing for medical purposes.Conclusion: These findings indicate that there is need for authorities to roll out a financial inclusion drive that will not only incentivise the financially excluded population to become included but that will also aim at promoting various financial products so that those who are already financially included have a wide range from which they can choose.Keywords: access, borrow, financial inclusion, financial hardships, healthcare, Saudi Arabia